Thunder-fire moxibustion for lumbar disc herniation: A systematic review and meta-analysis. Issue 49 (9th December 2022) - Chen, Jianye; Luo, Zongxiu; Liu, Mingda; Wang, Fusheng; Zhou, Rui; Wang, Ying; Jia, Yuyan; Wang, Xukai; Leng, Xiangyang
Abstract : Background: Lumbar disc herniation (LDH) is a common degenerative disease that severely impacts the quality of life of patients. Thunder-fire moxibustion is an ancient Chinese medicine-based external therapeutic procedure that has been employed for pain relief until this day. The focus of our study was to demonstrate the effectiveness and safety of thunder-fire moxibustion in the treatment of LDH. Methods: The literature databases searched included the Cochrane Library, Web of Science, Springer, PubMed, Wanfang digital periodicals database, China national knowledge infrastructure, VIP, and Chinese biomedical literature database, and the search period was from database creation to March 2022. These include randomized controlled trials of Thunder–Fire moxibustion alone or in combination with other therapies for LDH. Two evaluators independently extracted data. We accessed the quality of inclusive studies through a Cochrane risk of bias tool. Meta-analyses were performed using Review Manager (Version 5.5). Data was analyzed using fixed-effects or random-effects models, depending on the heterogeneity test results. Results: The meta-analysis included 17 studies involving 1344 patients with LDH. The analysis results were as follows: compared with other therapies, the efficacy of thunder-fire moxibustion was statistically significant; the total effective rate (RR = 1.20; 95%CI [1.15, 1.26]; P  < .00001), the Japanese orthopaedic association score (MD = 4.42; 95%CI [4.10, 4.73]; P  < .00001), the pain score (SMD = -2.66; 95% CI [-3.39, -1.94]; P  < .00001). Only 2 reported no adverse events in the included literature, and the remaining had no relevant records. The quality of the evidence in the 17 papers we examined was low or very low. Conclusion: Thunder–Fire moxibustion is effective in relieving discomfort in patients with LDH. It has significant clinical efficacy, but there is still a need for prospective, multicentre, large-sample randomized controlled trials to enhance the clinical evidence due to the quality of included studies and methodological limitations.